Inactive metallopeptidase homologs: the secret lives of pseudopeptidases - Lyons, Peter J. (Frontiers in Molecular Biosciences, 2024)
Inactive enzyme homologs, or pseudoenzymes, are proteins, found within most enzyme families, that are incapable of performing catalysis. Rather than catalysis, they are involved in protein-protein interactions, sometimes regulating the activity of their active enzyme cousins, or scaffolding protein complexes. Pseudoenzymes found within metallopeptidase families likewise perform these functions. Pseudoenzymes within the M14 carboxypeptidase family interact with collagens within the extracellular space, while pseudopeptidase members of the M12 “a disintegrin and metalloprotease” (ADAM) family either discard their pseudopeptidase domains as unnecessary for their roles in sperm maturation or utilize surface loops to enable assembly of key complexes at neuronal synapses. Other metallopeptidase families contain pseudopeptidases involved in protein synthesis at the ribosome and protein import into organelles, sometimes using their pseudo-active sites for these interactions. Although the functions of these pseudopeptidases have been challenging to study, ongoing work is teasing out the secret lives of these proteins.